The British party politics of Europe's future - Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2009)
The current turmoil in British politics has been a source of concern for many EU governments. The apparent instability of the Labour government, coupled with the Opposition Conservatives' sceptical attitude towards the EU's new institutional settlement, may induce the country's partners to loosen their links with the UK. Yet, continental states' gloomy prognoses about British European policy may be both unwarranted and self-fulfilling. Britain's partners must instead maintain their existing cooperation with the UK as well as take active advantage of the current flux in European policy-planning within the Conservative party
Keywords: 320